Conservation genetics of fish in Western Africa to improve regional fisheries management [résumé] - (:unkn) unknown (My University, 2016)
In western Africa, multiple species of marine fish are exploited by a large fishing community. The exploitation of this resource calls for the establishment of appropriate management and conservation strategies at national and regional levels, which must start with the correct species identification of catches at fish landing sites. To improve fisheries management in West Africa, research actions have recently been developed, but surveys for the correct identification of species and delimitation of stocks are still in need as e.g the famous sardinella shared stock between Morocco, Mauritania, Senegal, Gambia, Guinea Bissau. Research of the past two decades established that molecular approaches are the best to fill the need especially in poor data area. To address these challenges, we propose a research programme for improving the identification of catches following two objectives. The first objective is to implement a biodiversity collaborative survey on landing sites, with small scale fishermen, using a barcoding approach which will provide a reference barcode library for future studies. This objective may also help discovering new species, establish data base, follow inventory of genetic resources and identify taxonomic ambiguities as well as traceability of fishing product for e.g. exportation. The second is the development of appropriate molecular tools for the delimitation of potential genetic stocks in West Africa for selected fish of high economic importance. The project involves a network of collaborators which will facilitate different aspects of the study including collection/sampling and laboratory procedures. The outcomes of the project include the development of a molecular resource for West African fish, improvement of fisheries management particularly for transboundary species and a better understanding of their biodiversity along the East Atlantic. The project will also contribute to building human capacity in fish identification as wel
Keywords: African Research